Analisis Pengaruh PDRB, Investasi, Upah Minimum Provinsi Terhadap Penyerapan Tenaga Kerja Di Pulau Jawa - Dyah Indri Widyapangesti; Aris Soelistyo (Program Studi Ekonomi Pembangunan, 2022)
Geographically, the province on the island of Java is a strategic area for the national economy because of its more advanced economic growth and development compared to other regions and has a relatively high population. Regional differences on the island of Java which have their own characteristics that affect different development patterns, the island of Java is also inseparable from the history of regional infrastructure development on the island of Java which is far more advanced than other islands in Indonesia. This study aims to determine how big the influence of GDP, Domestic Investment, Foreign Investment, and the Provincial Minimum Wage on Labor Absorption in Java, partially or simultaneously. The results of this study GDP has a positive and significant effect on Labor Absorption, Domestic Investment (PMDN) has a positive and significant impact on Labor Absorption, Foreign Investment has a positive and significant impact on Labor Absorption, and the Provincial Minimum Wage has a positive and significant effect on Employment. has no positive and insignificant effect on Labor Absorption.